Effects of Castor Oil Nanoemulsion Extracted by Hexane on the Fourth Larval stage of Culex quinquefsciatus from Al Hawizeh Marsh/Iraq, and Non- Targeted Organism - Alla Abd Al Hassan Al Hilfy; Soolaf A. Kathiar; Hazim Idan Al Shammari (مجلة بغداد للعلوم)
The current study aims to show the importance of plant products as mosquitocides against Culex quinquefasciatus. Castor oil Nanoemulsions were subedit in various ratios including castor oil, ethanol, tween 80, and deionized water by using ultrasonication. Thermodynamic, centrifugation, PH, assay which improved that the formula  of 10 ml  of castor  oil, ethanol  5ml, tween 80 (14 ml) and deionized water 71ml was more stable than other formulas. The stable formula of castor oil nanoemulsion was characterized by transmission electron microscopy (TEM) and dynamic light scattering (DLS). Nanoemulsion droplets were spherical in shape and were found to have a Z-average diameter of 87.4nm. A concentration of castor oil nanoemulsion 250, 350, 450, and 550 ppm were tested as larvicidal agents and bulk emulsion 1000, 1500, 2000 , and 2500 ppm were tested also and compared, against the fourth instar larvae of C. quinquefasciatus. Castor oil nanoemulsion exhibited higher activity when compared to bulk emulsion. LC50 of castor oil nanoemulsion and castor bulk emulsion were found as 291.46 and 439.19ppm after 72 h, respectively. The toxic effects of castor oil bulk and Nano emulsion was tested against non-target organism Guppy fish and found to be not toxic at the concentration which used in the study.